Development and characterization of an in vitro model of colorectal adenocarcinoma with MDR phenotype. (25th March 2016) - Cinci, Lorenzo; Luceri, Cristina; Bigagli, Elisabetta; Carboni, Ilaria; Paccosi, Sara; Parenti, Astrid; Guasti, Daniele; Coronnello, Marcella
Abstract: The major cause of failure in cancer chemotherapy is the development of multidrug resistance (MDR), and the characterization of biological factors involved in this response to therapy is particularly needed. A doxorubicin‐resistant HCT‐8/R clone was selected from sensitive parental cells and characterized analyzing several parameters (cell cycle phase distribution, apoptotic activity, expression, distribution and functionality of the P‐gp efflux pump, the response to other chemotherapy agents, its ultrastructural features, invasiveness, and transcriptomic profile). HCT‐8/R cells showed a peculiar S phase distribution, characterized by a single pulse of proliferation, resistance to drug‐mediated apoptosis, increased expression and functionality of P‐gp and overexpression of stem cell markers (CD44 and aldehyde dehydrogenase 1A2). At the ultrastructural level, HCT‐8/R presented a greater cell volume and several intracytoplasmic vesicles respect to HCT‐8. Moreover, the resistant clone was characterized by cross resistance to other cytotoxic drugs and a greater capacity for migration and invasion, compared to parental cells. Our data reinforce the concept that the MDR phenotype in HCT‐8/R cells is multifactorial and involves multiple mechanisms, representing an interesting tool to understand the biological basis of MDR and to test strategies that overcome resistance to chemotherapy. Abstract : HCT‐8/R were fully characterized by multidisciplinary approaches. These approaches allowed to highlight poorly explored features of MDR phenotype. HCT‐8/R are suitable model to test novel therapeutic strategies.